Slash. Uri Caine’s Mahler - Poprawa, Adam (Interdisciplinary Studies in Musicology, 2018)
In recent years, artistic projects combining a wide array of musical styles, such as jazz interpretations of classical music or orchestral arrangements of rock songs, have enjoyed considerable popularity. As their authors were focused mainly on sales profits, the artistic value of their works was often highly disputable. Nevertheless, some outstanding achievements in that field have also been made, among them reinterpretations of classical repertoire - Bach, Beethoven, Mozart, Schumann, and, above all, Mahler - by American pianist Uri Caine. He recorded several CDs containing new versions of Mahler’s entire works or their excerpts. Sometimes Caine’s music moves far away from the originals, though such artistic experiments are always well-grounded and aesthetically convincing. Caine’s reinterpretations of Mahler have also some (auto)biographical overtones.